ELECTION VIOLATION AND ELECTION LAW ENFORCEMENT IN GENERAL ELECTION IN INDONESIA - Prawira, Syailendra Anantya (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
General Elections are the embodiments of the mandate stipulated in the 1945 Constitution of the Republic of Indonesia Article 1 paragraph (2) which affirms that